Sony targets laptop consumers in China : segment global or local? - Grayson, Kent; Waikar, Sachin ([London] : SAGE, 2016)
The manager of the Sony VAIO personal computer in China has been given two segmentation studies. One study is country-specific and product-specific. The other is a global segmentation study, which covers all regions and all of Sony's many consumer electronics. Which segmentation study should the manager rely on - or is there a way to rely on both? After deciding which study is best, which consumer should the manager target, and with what position?
Originally Published in: Grayson, K., & Waikar, S. (2011). Sony Targets Laptop Consumers in China: Segment Global or Local? (case revised 05/04/2012). 5-311-500. Evanston, IL: Kellogg School of Management.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; Soni Kabushiki Kaisha; Marketing -- Management -- Case studies; Marketing research -- Case studies